Spontaneous and frequent conformational dynamics induced by A…A mismatch in d(CAA)·d(TAG) duplex - Yogeeshwar Ajjugal (Nature Portfolio, 2021)
Abstract Base pair mismatches in DNA can erroneously be incorporated during replication, recombination, etc. Here, the influence of A…A mismatch in the context of 5′CAA·5′TAG sequence is explored using molecular dynamics (MD) simulation, umbrella sampling MD, circular dichroism (CD), microscale thermophoresis (MST) and NMR techniques. MD simulations reveal that the A…A mismatch experiences several transient events such as base flipping, base extrusion, etc. facilitating B–Z junction formation. A…A mismatch may assume such conformational transitions to circumvent the effect of nonisostericity with the flanking canonical base pairs so as to get accommodated in the DNA. CD and 1D proton NMR experiments further reveal that the extent of B–Z junction increases when the number of A…A mismatch in d(CAA)·d(T(A/T)G) increases (1–5). CD titration studies of d(CAA)·d(TAG)n=5 with the hZαADAR1 show the passive binding between the two, wherein, the binding of protein commences with B–Z junction recognition. Umbrella sampling simulation indicates that the mismatch samples anti…+ syn/+ syn…anti, anti…anti & + syn…+ syn glycosyl conformations. The concomitant spontaneous transitions are: a variety of hydrogen bonding patterns, stacking and minor or major groove extrahelical movements (with and without the engagement of hydrogen bonds) involving the mismatch adenines. These transitions frequently happen in anti…anti conformational region compared with the other three regions as revealed from the lifetime of these states. Further, 2D-NOESY experiments indicate that the number of cross-peaks diminishes with the increasing number of A…A mismatches implicating its dynamic nature. The spontaneous extrahelical movement seen in A…A mismatch may be a key pre-trapping event in the mismatch repair due to the accessibility of the base(s) to the sophisticated mismatch repair machinery.